PENGARUH LOCUS OF CONTROL DAN KOMITMEN PROFESIONAL PADA KINERJA AUDITOR INTERNAL - Putra, I Gusti Agung Mahendra; Latrini, Made Yenni (E-Jurnal Akuntansi, 2016)
This study aimed to analyze the influence of locus of control and professional commitment to the performance of internal auditors in the FIF GROUP Bali Province. This research was conducted in all branches FIF GROUP Bali Province eight branch offices located in Bali region by 2015 by making the internal auditor as many as 42 people as a sample by sample method saturated. The data collection is done by distributing questionnaires and analysis techniques using multiple linear regression. Based on the analysis, the variables locus of control and professional commitment to contribute as much as 82.1 percent on the performance of the internal auditor, while the remaining 17.9 percent is influenced by other variables not included in the model study. Through the analysis of the t test is known that the locus of control and professional commitment to positive effect on the performance of internal auditors in the FIF GROUP Bali Province.
Keywords: Locus Of Control, Professional Commitment, Performance Auditor